Association of high-sensitivity C-reactive protein in middle-aged and elderly Chinese people with hyperuricaemia and risk of coronary heart disease: a cross-sectional study - Xie, Mingsheng (BMJ Open, 2019)
OBJECTIVES: Patients with hyperuricaemia are at relatively high risk of developing coronary heart disease (CHD). The purpose of this study was to examine the relationship between high-sensitivity C-reactive protein (hs-CRP) and CHD risk in a middle-aged and elderly population with hyperuricaemia. DESIGN: A cross-sectional study. SETTING AND PARTICIPANTS: This study was conducted in a health examination centre of China. Participants were diagnosed with hyperuricaemia based on uric acid concentrations. Specifically, males with a uric acid concentration ≥416 μmol/L were included, as well as females with a concentration ≥360 μmol/L. MAIN OUTCOME MEASURES: 10-year CHD risk for each individual was evaluated using Framingham risk score based on the Adult Treatment Panel III charts. RESULTS: A total of 517 patients with hyperuricaemia (438 males and 79 females) aged from 40 to 85 years old were included in the present study. 193 (37.3%) patients were defined with relatively high 10-year CHD risk. Compared with the lowest quintile, the crude ORs of relatively high 10-year CHD risks were 1.43 (95% CI 0.78 to 2.63, p=0.245), 2.05 (95% CI 1.14 to 3.67, p=0.016), 2.77 (95% CI 1.54 to 4.98, p=0.001), 2.12 (95% CI 1.18 to 3.80, p=0.012) in the second, third, fourth and fifth quintiles of serum hs-CRP level, respectively (p for trend=0.057). The multivariable-adjusted ORs of relatively high 10-year CHD risk were 1.40 (95% CI 0.75 to 2.61, p=0.291) in the second, 2.05 (95% CI 1.13 to 3.72, p=0.019) in the third, 2.69 (95% CI 1.47 to 4.89, p=0.001) in the fourth and 2.10 (95% CI 1.15 to 3.84, p=0.016) in the fifth quintile of serum hs-CRP level when compared with the lowest quintile (p for trend=0.068). CONCLUSION: This study showed that ORs of relatively high 10-year CHD risk were raised in patients with hyperuricaemia with higher serum hs-CRP level; however, there was a not significant but borderline trend association and that more research is needed.